CYTOKINESIS-BLOCK MICRONUCLEUS ASSAY IN HUMAN GLIOMA CELLS EXPOSED TO RADIATION - Slowinski, Jerzy; Bierzynska-Macyszyn, Grazyna; Mazurek, Urszula; Widel, Maria; Latocha, Malgorzata; Stomal, Monika; Snietura, Miroslaw; Mrowka, Ryszard (Image Analysis and Stereology, 2011)
Biological tests are efficient in reflecting the biological influences of several types of generally harmful exposures. The micronucleus assay is widely used in genotoxicity studies or studies on genomic damage in general. We present methodological aspects of cytokinesis-block micronucleus assay performed in human gliomas irradiated in vitro. Eight human glioblastoma cell lines obtained from DSMZ (Deutsche Sammlung von Mikroorganismen und Zellkulturen GmbH, Germany) were gamma-irradiated (60Co) over a dose range of 0-10 Gy. Cytokinesis-block micronucleus assay was performed to quantitate cytogenetic damage. The cells were fixed directly on dishes, stained with fluorochrome DAPI and evaluated under fluorescent and phase contrast microscope. The micronucleus frequency was expressed as a micronuclei (MN) per binucleated cell (BNC) ratio, calculated after scoring at least 100 BNC per dish. The frequency of spontaneous MN ranged from 0.17 to 0.613 (mean: 0.29 ± 0.14). After irradiation increase of MN frequency in the range of 0.312 - 2.241 (mean: 0.98 ± 0.68) was found at 10 Gy. Gliomas are extremely heterogenous in regard to cytogenetic effects of irradiation, as shown in this study by cytokinesis-block micronucleus assay. This test is easily performed on irradiated glioma cell lines and can assist in determining their radiosensitivity. However, in order to obtain reliable and reproducible results, precise criteria for MN scoring must be strictly followed. Simultaneous use of fluorescent and phase contrast equipment improves imaging of morphological details and can further optimize MN scoring.